JALAN RAYA POS (ANYER-PANARUKAN) SEBAGAI BUKTI DARI KEBIJAKAN DAENDELS YANG MASIH ADA HINGGA SEKARANG - Febriana Pulungan, Dona; Sari Harahap, Armyla; Zahrah, Alfiyyah; Sinaga, Rosmaida (Department of History Education, Faculty of Social Science, Universitas Negeri Medan, 2025)
This study aims to determine the background to the construction of the Post Highway (Aanyar-Panarukan) and the impact of the Post Highway Development. This research uses the historical method with stages consisting of Heuristics, VeriKication, Interpretation and Historiography. Based on the research results, it is known that the background to the construction of the Postal Highway was to strengthen military defenses during the reign of Herman Willem Daendels against British attacks on the island of Java and to build transportation facilities. The impact of the construction of the Postal Highway is to increase the progress of the community's economy and the development of transportation which improves the distribution of community goods.